PERAN RUANG TRANSISI DALAM PENDINGINAN PASIF HUNIAN - Dian Sekartaji; Yuji Ryu (NALARs, 2026)
Traditional Japanese houses, or Minka, represent a culturally rich and climate-responsive architectural form that has long demonstrated effective passive cooling strategies. Among their many features, the Doma, a ground-level, unboarded floor area typically located near the entrance—serves as a thermal buffer that can significantly influence indoor temperature dynamics. This study explores the passive cooling potential of the Doma through a combined approach of field measurement and simulation, using the U House in Koyanose, Kitakyushu, as a case study. Temperature and humidity data were collected over a one-week period during the summer season, focusing on the spatial relationship between the doma and adjacent tatami rooms. The results revealed that the Doma consistently maintained lower air temperatures than the surrounding living spaces and contributed to a reduction in temperatures in nearby rooms. To identify the optimal spatial configuration for cooling, simulations were conducted using DesignBuilder software to evaluate three different Doma placements: north (existing), east, and south. Among these, the southern Doma placement yielded the lowest average indoor temperatures across all tested rooms, achieving reductions of up to 1.3°C during the daytime compared to the original layout. These findings underscore the Doma’s potential as a cost-effective and culturally embedded passive cooling strategy. The study contributes to sustainable architectural practices by illustrating how vernacular design elements can be adapted and optimized using modern simulation tools. As global temperatures continue to rise, integrating such passive design principles into both traditional and contemporary buildings offers a promising pathway for enhancing thermal comfort and reducing energy consumption.